Rhabdomyosarcoma in adults with severe thrombocytopenia: Challenges in clinical management and therapeutic complications - Jose Luis Estela-Zape; Valeria Sanclemente-Cardoza; Leonardo Arzayus-Patiño; Lizeth Dayana Noreña-Buitrón; María Alejandra Espinosa (Respiratory Medicine Case Reports)
Alveolar rhabdomyosarcoma (ARMS) in adults is a rare condition with a poor prognosis compared to other subtypes. The management of this pathology is complex due to the lack of standardized guidelines and the limited response to multimodal treatments, including chemotherapy, radiotherapy, and surgery. We report the case of a 40-year-old male with stage IV ARMS and pulmonary metastasis, who underwent resection of right supraclavicular sarcoma and cervical lymph node dissection. He was later referred for palliative chemotherapy following an acute clinical presentation lasting two days, characterized by right facial edema, inflammation, ulceration, and severe pain. Initial treatment included ampicillin/sulbactam, trimethoprim/sulfamethoxazole, and dexamethasone. Chemotherapy with doxorubicin and ifosfamide was delayed due to thrombocytopenia, elevated D-dimer and fibrinogen levels, and an echocardiographic finding that required differentiation between thrombus and metastatic lesion. Anticoagulation with fondaparinux and transfusions were initiated, and the patient received 10 sessions of radiotherapy. During hospitalization, the patient developed orthopnea, pleural effusion, superior vena cava syndrome, and hemodynamic deterioration, necessitating vasopressor support and mechanical ventilation. Despite these interventions, the patient progressed to refractory shock, severe hypoxemia, and died from cardiac arrest. This case highlights the challenges in managing ARMS in adults with severe thrombocytopenia.